Change in phosphorus requirement with increasing grain yield for rice under saline-sodic stress in Northeast China - Wei, Zhanxi; Zhang, Yi; Liu, Zhanfeng; Peng, Mengsu; Wang, Teng; Cao, Ning (Frontiers in Environmental Science, 2022)
It is possible to simultaneously reduce both food security and environmental impact by understanding the relation between rice (Oryza sativa L.) grain yield and phosphorus (P) uptake requirements. The goal of this study was to determine P uptake requirements and relationship of P accumulation with yield formation at different rice grain yield levels under saline-sodic stress. A database comprising measurements in 28 plots in 4 on-farm research station located in saline-sodic soil area during the period 2018-2019 in Jilin province of Northeast China was used for the analyses. The grain yields of rice averaged 9.0 Mg ha-1 and varied from 5.11 to 13.41 Mg ha-1. The P uptake at late growth stages (heading and maturity) of rice gradually increased with increasing grain yield levels. The P requirement for producing 1 Mg grain (Preq.) were 4.61, 4.60, and 4.21 kg Mg-1 for grain yields ranging from <7.0, 8.0–9.5, and >10 Mg ha−1, respectively. The decrease in Preq. values with increasing grain yield was mainly attributable to the increase in the harvest index from 0.25 to 0.33. A larger proportion of the P was accumulated from heading to maturity stage when grain yields were higher than 8.0 Mg ha−1. The P uptake in leaves, stems and panicles at the maturity stage gradually increased with increasing grain yield levels. The results give a contribution to rice production in saline-sodic soils, and greatly optimize P management especially in high-yielding rice systems, furtherly improving food security in the Jilin province of China.